Enuresis and more. Issue 5 (9th July 2013) - Lee, T W R; Duff, A J A; Martin, T; Barrett, J M
Abstract : We describe Pervasive Refusal Syndrome, an important but rare, debilitating condition that may present to paediatric services. Although previous reports have described improvement seen with care delivered in the mental health setting, we have demonstrated treatment predominately delivered in a paediatric ward environment associated with successful recovery.